Melodic Intonation Therapy on Non-fluent Aphasia After Stroke: A Systematic Review and Analysis on Clinical Trials - Zhang, Xiaoying; Li, Jianjun; Du, Yi (Frontiers in Neuroscience, 2022)
Melodic Intonation Therapy (MIT) is a melodic musical training method that could be combined with language rehabilitation. However, some of the existing literature focuses on theoretical mechanism research, while others only focus on clinical behavioral evidence. Few clinical experimental studies can combine the two for behavioral and mechanism analysis. This review aimed at systematizing recent results from studies that have delved explicitly into the MIT effect on non-fluent aphasia by their study design properties, summarizing the findings, and identifying knowledge gaps for future work. MIT clinical trials and case studies were retrieved and teased out the results to explore the validity and relevance of these results. These studies focused on MIT intervention for patients with non-fluent aphasia in stroke recovery period. After retrieving 128 MIT-related articles, 39 valid RCT studies and case reports were provided for analysis. Our summary shows that behavioral measurements at MIT are excessive and provide insufficient evidence of MRI imaging structure. This proves that MIT still needs many MRI studies to determine its clinical evidence and intervention targets. The strengthening of large-scale clinical evidence of imaging observations will result in the clear neural circuit prompts and prediction models proposed for the MIT treatment and its prognosis.